Taenia solium taeniosis and cysticercosis literature in Tanzania provides research evidence justification for control: A systematic scoping review. - Helena Aminiel Ngowi; Andrea Sylvia Winkler; Uffe Christian Braae; Robinson Hammerthon Mdegela; Ernatus Martin Mkupasi; Mwemezi Lutakyawa Kabululu; Faustin Peter Lekule; Maria Vang Johansen (PLoS ONE)
Background Despite Taenia solium taeniosis/cysticercosis (TSTC) having been put high on the global agenda of neglected tropical diseases (NTDs), which over the last years has received a lot of attention, there has been no control programmes in place in sub-Saharan Africa, a highly endemic region. This could be attributed to lack of awareness of many stakeholders on the burden and impact of T. solium. This information is essential in guiding TSTC policies, practices and research agendas as well as encouraging cross-sectoral collaboration in the control of this important zoonotic parasite using a One Health approach. National elimination of the parasite is the foundation for global eradication. This will require that substantial country-level information is provided to all key stakeholders. We have mapped out TSTC research evidence in Tanzania to inform on disease burden and potential for integrated control measures. Methodology/principal findings A scoping review of all TSTC studies undertaken in Tanzania and published up to December 2018 was conducted. The articles were searched from PUBMED, AJOL, Google Scholar and Google in general. Fifty-one (51) articles met the inclusion criteria and were reviewed. Prevalence of taeniosis of 2.3% - 5.2% was estimated based on copro-antigen ELISA while human cysticercosis of >16% was estimated based on serum antigen ELISA (Ag-ELISA) or IgG Western Blot. Neurocysticercosis (NCC) contributed significantly to epilepsy in adults. Farm prevalence of porcine cysticercosis were 6.0% - 17.4% (lingual examination) and 1.5% - 33.3% (Ag-ELISA). Slaughter-slab prevalence were 0% - 18.2% (routine meat inspection). Lacking latrines, watering pigs with river or pond water, and feeding pigs with potato peels were associated with porcine cysticercosis prevalence. Washing hands by dipping method increased the risk of human cysticercosis. In 2012, the number of DALYs/1000 person-years for NCC-associated epilepsy was 0.7 (95% UI, 0.2-1.6), around 5 million USD (95% UI, 797,535-16,933,477) were spent due to NCC-associated epilepsy and nearly 3 million USD (95% UI, 1,095,960-5,366,038) were potentially lost due to porcine cysticercosis. Three rounds of annual treatment of school-age children with praziquantel significantly reduced prevalence of taeniosis and porcine cysticercosis. Health education was efficacious in improving knowledge and attitudes favourable for control of TSTC while a single dose of oxfendazole 30 mg/kg body weight was efficacious in eliminating T. solium cysticerci from pig musculature. Conclusions/significance The observed high burden of TSTC and the significant contribution of NCC to epilepsy in Tanzania warrant urgent interventions. Evaluation of best control options should make use of disease transmission dynamics models such as cystiSim, taking into account findings from the field based intervention studies. In addition, locally adapted management guidelines for people suffering from NCC are urgently needed.